The transformation of political communication in China from propaganda to hegemony - Zhang, Xiaoling, Dr.; ProQuest (Firm) (Hackensack, N.J. : World Scientific, 2011)
"This book examines different dynamics such as marketisation, globalisation and new media technologies that have driven the transformation of China's media industry--one of the primary battlegrounds where ideological, social and economic struggles are fought--against the backdrop of the growing tensions between economic growth, globalisation, and political control in China."--
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Mass media policy -- China; Communication policy -- China; Communication -- Political aspects -- China; Communication in politics -- China; Electronic books